The Sensitive Reference Interview - Ondrusek, Anita; Ren, Xiaoai (My University, 2015)
Answering sensitive reference questions can be a challenging task for reference librarians since it involves complicated ethical and policy concerns. The facets of a sensitive reference interview may include a sensitive patron, a sensitive patron request, a sensitive reference librarian, and a sensitive reply. Therefore, conducting a sensitive reference interview requires knowledge, training and practice. In addition, in order to act professionally during the sensitive reference interviews, reference librarians must be familiar with the relevant policies, regulations, and laws as well as the guidelines created by professional organizations on providing sensitive reference services. This booklet was created to guide public librarians through a training session on the sensitive reference interview. It contains brief summaries of, and references to, regulations and guidelines published by professional organizations and multiple-type libraries, and the applicable Georgia codes. Appendices include a checklist for librarians, advice on addressing requests for consulting directories for customized information, and a list of practice exercises based sensitive reference vignettes.